Potential Toxicity Of Some Plant Metanol Extracts Against Aedes aegepti (L). Larvae - Ernaldi Eka Nanda; Entun Santosa; Danar Dono (CROPSAVER, 2018)
Resistance is a decrease in the level of sensitivity of a pest populations that causing a previously effective pesticides becoming ineffective. This case is caused by inappropriate insecticides application, continuous use, only one type of pesticide and usage for long periods of time. There are a lot alternative source of insecticides which is more effective and environmentally friendly. One alternative source of insecticides that can be used for pest control is plants. This study aimed to determine the potential toxicity of methanol extract of N. tabacum, B. asiatica, V. zizanoides, A. indica, and T. vogelli on the mortality and development time of A. aegypti mosquito larvae. The research was conducted at the Laboratory of Pesticides and Environmental Toxicology, Department of Plant Pests and Diseases, Faculty of Agriculture, Padjadjaran University, Jatinangor. The experiment was performed using a Completely Randomized Design (CRD) with 6 treatment and 4 replication. The result showed that methanol extracts of the test material were toxic to the larvae A. aegypti with the highest the lowest toxicity were at the concentration of 0.001% i.e treatment of T. vogelli, N. tabacum, B. asiatica, A. indica, and V. zizanoides with the successive rate of mortality (45%, 65%), (37.5%, 60%), (32.5%, 50%) and (32,5%, 47.5%). Besides being toxic, the methanol extract also influenced development of A. aegypti larvae. The pH levels and the dissolved oxygen content of the tested methanol extract solution at the concentration of 0.005% in each treatment are not much different when compare with controls.